1999
DOI: 10.1055/s-2006-960840
|View full text |Cite
|
Sign up to set email alerts
|

In VitroInducible Nitric Oxide Synthesis Inhibitory Active Constituents fromFraxinus rhynchophylla

Abstract: Bioassay-guided fractionation of an H2O extract of the barks of Fraxinus rhynchophylla has furnished two inducible nitric oxide synthase (iNOS) inhibitory compounds, ferulaldehyde (1) and scopoletin (3) together with a coumarin, fraxidin (2). Compounds 1 and 3 showed inhibition of nitric oxide (NO) synthesis in a dose-dependent manner by murine macrophage-like RAW 264.7 cells stimulated with interferon-gamma (IFN-gamma) plus lipopolysaccharide (LPS). The inhibition of NO synthesis of 1 was reflected in the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 2 publications
0
28
0
Order By: Relevance
“…Fraxidin methyl ether showed the highest enhancement of cell viability (29.4%) among tested 18 chemicals. Fraxidin with a coumarinic moiety has been reported to have several beneficial properties, including antioxidant, anti-inflammatory, and anti-diabetogenic effects (Kimura et al, 1985;Kim et al, 1999;Fort et al, 2000). In polymorphonuclear leukocytes, fraxidin inhibited the formation of the cyclooxygenase product, hydroxy-5,8,10-heptadecatrienoic acid (HHT), strongly by inhibition of the formation of 5-hydroxy-6,8,11,14-eicosatetraenoic acid from arachidonic acid (Kimura et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraxidin methyl ether showed the highest enhancement of cell viability (29.4%) among tested 18 chemicals. Fraxidin with a coumarinic moiety has been reported to have several beneficial properties, including antioxidant, anti-inflammatory, and anti-diabetogenic effects (Kimura et al, 1985;Kim et al, 1999;Fort et al, 2000). In polymorphonuclear leukocytes, fraxidin inhibited the formation of the cyclooxygenase product, hydroxy-5,8,10-heptadecatrienoic acid (HHT), strongly by inhibition of the formation of 5-hydroxy-6,8,11,14-eicosatetraenoic acid from arachidonic acid (Kimura et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It is to be expected that fraxidin can reduce tissue edema and inflammation. Moreover fraxidin inhibited the formation of inducible nitric oxide synthase (Kim et al, 1999) and showed antihyperglycemic activity (Fort et al, 2000). These 7 chemicals including fraxidine were selected as primary hits since those were considered as chemicals showing significant enhancement of viability in comparison with fraxin.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] In the course of screening adipocyte differentiation-inhibitory activity of natural products employing the mouse preadipocyte cell line, 3T3-L1 as an in vitro assay system, the EtOAc fraction of F. rhynchophylla showed significant inhibitory activity on adipogenesis. Thus, in the present study, we attempted to isolate the active constituents from F. rhynchophylla and evaluate their inhibitory activity.…”
Section: -3)mentioning
confidence: 99%
“…In addition, diuretic, anticoagulant and antiallergic effects have been reported by pharmacological studies. 12,13) Related to its chemical constituents, coumarins are the characteristic constituents of Fraxinus species and responsible for the diverse activity such as antivirus and anti-inflammatory activity. 14,15) Besides coumarins, other constituents such as lignans, secoiridoid glycosides and other phenolic compounds were also reported.…”
mentioning
confidence: 99%
“…Fraxinus rhynchophylla was used for eye disease, eclampsia, dysentery, asthma, bronchitis and leucorrhea. Kim et al 8) found that F. rhynchophylla could furnish two inducible nitric oxide synthase (iNOS) inhibitory compounds preventing nitric oxide (NO) synthesis. Moreover, oleuropein ( Fig.…”
mentioning
confidence: 99%